Dietary Vitamin K1 intake is associated with lower long-term fracture-related hospitalization risk: the Perth longitudinal study of ageing women. Issue 20 (28th September 2022) - Sim, Marc; Strydom, Andre; Blekkenhorst, Lauren C.; Bondonno, Nicola P.; McCormick, Rachel; Lim, Wai H.; Zhu, Kun; Byrnes, Elizabeth; Hodgson, Jonathan M.; Lewis, Joshua R.; Prince, Richard L.
Abstract : In multivariable-adjusted models including plasma Vitamin D, higher dietary Vitamin K1 (∼≥100 μg d −1 ) was associated with lower risk for any fracture (A) and hip fracture-related hospitalizations (B) over 14.5 years in community-dwelling older women. Abstract : This study examined the association between dietary Vitamin K1 intake with fracture-related hospitalizations over 14.5 years in community-dwelling older Australian women ( n = 1373, ≥70 years). Dietary Vitamin K1 intake at baseline (1998) was estimated using a validated food frequency questionnaire and a new Australian Vitamin K nutrient database, which was supplemented with published data. Over 14.5 years, any fracture ( n = 404, 28.3%) and hip fracture ( n = 153, 10.7%) related hospitalizations were captured using linked health data. Plasma Vitamin D status (25OHD) and the ratio of undercarboxylated osteocalcin (ucOC) to total osteocalcin (tOC) from serum was assessed at baseline. Estimates of dietary Vitamin K1 intake were supported by a significant inverse association with ucOC : tOC; a marker of Vitamin K status ( r = −0.12, p < 0.001). Compared to women with the lowest Vitamin K1 intake (Quartile 1, <61 μg d −1 ), women with the highest Vitamin K1 intake (Quartile 4, ≥99 μg d −1 ) had lower hazards for any fracture- (HR 0.69 95%CI 0.52–0.91, p < 0.001) and hip fracture-related hospitalization (HR 0.51 95%CI 0.32–0.79, p < 0.001), independent of 25OHD levels, as part of multivariable-adjusted analysis. Spline analysis suggested a nadir in the relative hazard for any fracture-related hospitalizations at a Vitamin K1 intake of approximately 100 μg day −1 . For hip fractures, a similar relationship was apparent. Higher dietary Vitamin K1 is associated with lower long-term risk for any fracture- and hip fracture-related hospitalizations in community-dwelling older women.